Mcm2 hypomorph leads to acute leukemia or hematopoietic stem cell failure, dependent on genetic context. Issue 9 (3rd August 2022) - Matsukawa, Toshihiro; Yin, Mianmian; Baslan, Timour; Chung, Yang Jo; Cao, Dengchao; Bertoli, Ryan; Zhu, Yuelin J.; Walker, Robert L.; Freeland, Amy; Knudsen, Erik; Lowe, Scott W.; Meltzer, Paul S.; et al.
Abstract: Minichromosome maintenance proteins (Mcm2‐7) form a hexameric complex that unwinds DNA ahead of a replicative fork. The deficiency of Mcm proteins leads to replicative stress and consequent genomic instability. Mice with a germline insertion of a Cre cassette into the 3′UTR of the Mcm2 gene (designated Mcm2 Cre ) have decreased Mcm2 expression and invariably develop precursor T‐cell lymphoblastic leukemia/lymphoma (pre‐T LBL), due to 100–1000 kb deletions involving important tumor suppressor genes. To determine whether mice that were protected from pre‐T LBL would develop non‐T‐cell malignancies, we used two approaches. Mice engrafted with Mcm2 Cre/Cre Lin − Sca‐1 + Kit + hematopoietic stem/progenitor cells did not develop hematologic malignancy; however, these mice died of hematopoietic stem cell failure by 6 months of age. Placing the Mcm2 Cre allele onto an athymic nu / nu background completely prevented pre‐T LBL and extended survival of these mice three‐fold (median 296.5 vs. 80.5 days). Ultimately, most Mcm2 Cre/Cre ; nu / nu mice developed B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL). We identified recurrent deletions of 100–1000 kb that involved genes known or suspected to be involved in BCP‐ALL, including Pax5, Nf1, Ikzf3, and Bcor . Moreover, whole‐exome sequencing identified recurrent mutations of genes known to be involved in BCP‐ALL progression, such as Jak1 / Jak3, Ptpn11, and Kras . These findings demonstrate that an Mcm2 Cre/Cre hypomorph can induce hematopoietic dysfunction via hematopoietic stem cell failure as well as a "deletor" phenotype affecting known or suspected tumor suppressor genes.